2012
DOI: 10.1080/1068316x.2011.561801
|View full text |Cite
|
Sign up to set email alerts
|

Minimization and maximization techniques: assessing the perceived consequences of confessing and confession diagnosticity

Abstract: Identifying interrogation strategies that minimize the likelihood of obtaining false information, without compromising the ability to elicit true information, is a challenge faced by both law enforcement and scientists. Previous research suggests that minimization and maximization techniques may be perceived by a suspect as an expectation of leniency and a threat of harsher punishment, respectively, and that these approaches may be associated with false confessions. The current studies examine whether it is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 11 publications
4
88
1
4
Order By: Relevance
“…When the evidence is strong, suspects are more likely to confess (Cassell and Hayman 1996;Moston et al 1992). Certain police techniques such as adoption of a humanitarian approach (Holmberg and Christianson 2002;Kebbell et al 2010), minimization and maximization (Horgan et al 2012), and showing understanding of the suspect's actions (Kebbell et al 2010) also help to elicit confessions from guilty suspects.…”
Section: Factors Related To Confessionsmentioning
confidence: 96%
“…When the evidence is strong, suspects are more likely to confess (Cassell and Hayman 1996;Moston et al 1992). Certain police techniques such as adoption of a humanitarian approach (Holmberg and Christianson 2002;Kebbell et al 2010), minimization and maximization (Horgan et al 2012), and showing understanding of the suspect's actions (Kebbell et al 2010) also help to elicit confessions from guilty suspects.…”
Section: Factors Related To Confessionsmentioning
confidence: 96%
“…The strong belief in "guilt" on the part of interrogators has been shown to lead to the use of longer interrogations that involve more psychologically manipulative tactics-ultimately leading to the elicitation of both true and false confessions that confirm the beliefs of the interrogator (see Kassin et al 2003;Kassin 2002, 2004;Narchet et al 2011). The psychological manipulation of consequences in this context, and the associated manipulation of perceived culpability on the part of the suspect, have been shown to directly influence the incidence of false confessions (see Horgan et al 2012).…”
Section: Introductionmentioning
confidence: 96%
“…,Beune et al (2009; see also Beune 2009), Forrest et al (2006,Horgan et al (2012),Horselenberg et al (2003),Kebbell and Daniels (2006),,Klaver et al (2008),Nash andWade (2009), andvan Bergen et al (2008). Three of these studies were conducted in the United States, two in Australia, three in the Netherlands, and one each in the United Kingdom and Canada.…”
mentioning
confidence: 94%
“…Both minimization and maximization have been linked to false confessions (see Horgan et al, 2012). Kassin and McNall (1991) showed that the use of maximization and minimization changes participants' perceptions of the consequences of a suspect confessing.…”
Section: Situational Factors Associated With False Confessionsmentioning
confidence: 99%
“…The rapport scripts were developed based on previous rapport studies (Vallano & Schreiber Compo, 2011; and on rapport building techniques that have been recommended by researchers and reportedly used by police investigators (Fisher & Geiselman, 1992;Kelly et al, 2013;Vallano et al, 2014). The interrogation scripts were developed based on the scripts used in previous interrogation studies (Horgan et al, 2012;Guyll et al, 2013;Russano et al, 2005).…”
Section: Materials and Measuresmentioning
confidence: 99%